2010
DOI: 10.1021/cg900830y
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Model for Nucleation Kinetics Determination in Droplet-Based Microfluidic Systems

Abstract: The measured induction times in droplet-based microfluidic systems are stochastic and are not described by the deterministic population balances or moment equations commonly used to model the crystallization of amino acids, proteins, and active pharmaceutical ingredients. A stochastic model in the form of a Master equation is formulated for crystal nucleation in droplet-based microfluidic systems for any form of nucleation rate expression under conditions of time-varying supersaturation. An analytical solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
201
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(206 citation statements)
references
References 46 publications
(155 reference statements)
5
201
0
Order By: Relevance
“…Accordingly, at each set of conditions a distribution of induction times is obtained similar to studies reported in the literature. [14][15][16] To smoothe the data a lognormal function was fitted to each distribution, giving a very reasonable fit. Lognormal distributions are seen in many data sets from different scientific disciplines, and are indicative of random variation resulting from multiple independent factors which have a multiplicative effect on the measured quantity.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, at each set of conditions a distribution of induction times is obtained similar to studies reported in the literature. [14][15][16] To smoothe the data a lognormal function was fitted to each distribution, giving a very reasonable fit. Lognormal distributions are seen in many data sets from different scientific disciplines, and are indicative of random variation resulting from multiple independent factors which have a multiplicative effect on the measured quantity.…”
Section: Methodsmentioning
confidence: 99%
“…For crystallization in a nanoliter droplet implemented in a microfluidic platform [18,19,31], the small scale of the system inhibits implementing conventional methods of probing the solute concentration. While visual observation of the dynamics in self-assembled systems could be accessible through advanced microscopes (such as the fluorescent imaging technique used to track the real-time movement and clustering of Janus particles [32]), such information has to be translated into a variable that can represent the assembly status for control.…”
Section: Limited Sensors For Real-time Measurementsmentioning
confidence: 99%
“…The crystallization of crystals in small volumes requires the use of stochastic models (e.g., [31]). The nucleation and growth processes for the microfluidic platform in Fig.…”
Section: Closed-loop Controlmentioning
confidence: 99%
See 2 more Smart Citations